The Role of Media in the Repression–Protest Nexus: A Game-theoretic Model. (September 2015) - Kim, HeeMin; Whitten-Woodring, Jenifer; James, Patrick
Idealized independent media function as "watchdogs." Indeed, human rights nongovernmental organizations have argued that media freedom will improve human rights. This makes sense intuitively, yet recent formal and empirical studies show that the effect of independent media varies across regime types. We explore the relationship among media, government, and citizen protest movements and employ a game-theoretic model to investigate how the equilibria vary depending on regime type and media independence. In terms of equilibrium, we find that media watchdogging is most active in autocracies (and not in democracies), especially when the government's perceived capability to repress public protest is declining. Uncertainty about the government's ability to repress plays a central role in accounting for the manifestation of media watchdogging in conjunction with public protest. Illustrations from Tunisia and North Korea are provided to highlight equilibria derived from the formal model that vary as a product of perceptions about the government's ability to repress.